Readers’ Theatre: An Organic Inquiry in Alaska Awakening Possibilities in a Living Spiral of Understanding - Melany Cueva (Adult Education Research Conference, 2007)
Organic Inquiry, as the qualitative research design method, provided for a richness of data to more fully appreciate how 24 diverse adult learners in Alaska described their experience with Readers’ Theatre as cancer education both during a workshop and over time that allowed for reflection and contemplation.